From hunter‐gatherers to food producers: New dental insights into the Nile Valley population history (Late Paleolithic–Neolithic) - Nicolas Martin; Adrien Thibeault; Lenka Varadzinová; Stanley H. Ambrose; Daniel Antoine; Petra Brukner Havelková; Honegger, Matthieu; Joel D. Irish; Piotr Osypiński; Donatella Usai; Nicolas Vanderesse; Ladislav Varadzin; et al. (My University, 2024)
AbstractObjectivesThis study presents biological affinities between the last hunter‐fisher‐gatherers and first food‐producing societies from the Nile Valley. We investigate odontometric and dental tissue proportion changes between these populations from the Middle Nile Valley and acknowledge the biological processes behind them.Materials and MethodsDental remains of 329 individuals from Nubia and Central Sudan that date from the Late Pleistocene to the mid‐Holocene are studied. Using 3D imaging techniques, we investigated outer and inner metric aspects of upper central incisors, and first and second upper molars.ResultsLate Paleolithic and Mesolithic foragers display homogeneous crown dimensions, dental tissue proportions, and enamel thickness distribution. This contrasts with Neolithic trends for significant differences from earlier samples on inner and outer aspects. Finally, within the Neolithic sample differences are found between Nubian and Central Sudanese sites.DiscussionSubstantial dental variation appears to have occurred around 6000 bce in the Nile Valley, coinciding with the emergence of food‐producing societies in the region. Archeological and biological records suggest little differences in dietary habits and dental health during this transition. Furthermore, the substantial variations identified here would have happened in an extremely short time, a few centuries at most. This does not support in situ diet‐related adaptation. Rather, we suggest these data are consistent with some level of population discontinuity between the Mesolithic and Neolithic samples considered here. Complex settlement processes could also explain the differences between Nubia and Central Sudan, and with previous results based on nonmetric traits.